Fear of falling and self-perception of health in older participants and non-participants of physical activity programs - Carolina Kruleske da Silva; Celita Salmaso Trelha; Rubens Alexandre da Silva Junior (Universidade Estadual Paulista (UNESP), 2013)
Fear of falling, self-perception of health, and participation in physical activity programs have been associated with several variables related to health and performance in older adults. The purpose of this study was to evaluate self-perception of health and fear of falling in older adult participants and non-participants of physical activity programs, and to verify the relationship between these variables. A total of 40 healthy but sedentary older adults, and 45 physically active older adults were assessed through the Falls Efficacy Scale International-Brazil (FES-I) and a questionnaire that measured their self-perception of health. The older adults that did not participate in regular physical activity programs presented higher scores of fear of falling, which, in turn, is associated with an increase of risk for falls. Moreover, older adults, participants in regular physical activity programs exhibited a more positive health perception than did the non-participants. Also, non-participants of physical activity programs perceived their health status as being poor or very poor as well as expressing great concern about falling compared to those who considered their health as excellent, good or regular. The results of this study have important implications for making clinical decisions in prevention or rehabilitation of older people, and they justify recommendations to the public health system.